Identifying and evaluating causes of waste effect in green building projects - Usama Hamed Issa; Ahmed Gamal AbdelHaffez; Alaa Atif Abdel-Hafez; Kamal Abbas Assaf (Journal of Engineering and Applied Science)
Abstract Green building (GB) projects in the Middle East face several causes of waste that occur during design and construction stages. These causes affect the objectives of GB projects (economic, environmental, and social). Therefore, this research aims to define causes of waste in GB projects and evaluate the effect of these causes on the objectives of GB projects. Forty-five causes of waste are determined and classified into five main groups as follows: (G01) green materials, (G02) green building design, (G03) sustainable site, (G04) green building technologies, and (G05) green building stakeholders. Through field surveys, including semi-structured interviews and brainstorming sessions, the probability of occurrence for each cause of waste and impact on the economic, environmental, and social objectives are evaluated, as well as the waste severity is determined based on a combined effect of probability and impacts. The correlations among the waste indices are assessed, and the highest correlation is observed between probability and economic followed by economic and social objective. The results show that the most significant cause of waste that has the highest value for economic, environmental, and social objectives is “Poor assessment of site conditions before design, such as topography, hydrology, climate, vegetation, and soil.” Group 05 has the maximum number of critical causes of waste, which is considered the most significant group, due to its high values related to all objectives. Results indicate that the economic objective is classified as the most affected one by the causes of waste, followed by the environmental objective.